The attitude of the People’s Labor Union of Russian Solidarists and its subsidiaries to national administrative construction in 1987–1998 - M. S. Novikov (Омский научный вестник: Серия "Общество. История. Современность")
The People’s Labor Union of Russian Solidarists is the least popular among Russian historians of organizations operating on the territory of the Russian Federation. Formed in Serbia in 1930, by emigrants, it was the oldest Russian national organization opposing the communist regime in the USSR. During the years of perestroika, the solidarists were unable to create a unified party structure in the Russian Soviet Federative Socialist Republic and act independently. As a result, the organization collaborated with anti-communists from «Democratic Russia», influenced the formation of the Russian Christian Democratic Movement. Members of the People’s Labor Union of Russian Solidarists actively participated in the discussion of economic and social issues relevant to the new statehood, including national administrative construction. The analysis of the organization’s documents, memoirs of its participants, and party journalism allow us to conclude that the lack of a unified program for the transformation of the country, focusing primarily on criticism of the Soviet experience, led to the transformation of the organization into a «discussion club» with further disappearance from the political life of the country. However, the created atmosphere of rejection of the national administrative reforms of the USSR led the solidarists and their supporters to justify and glorify the dissolution of the USSR, the loss of a number of territories and the creation of numerous points of confrontation between the federal government and the subjects of the federation.